NATIONAL LANGUAGE AND LITERARY VARIANT - Abdulazizova Sevara Ganiyevna; Axmadjonova Oydinoy; No'monjonova Gulnoza (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This  article  explores  the  relationship  between  the  national  language  and  its literary  variant,  focusing  on  their  roles  in  cultural identity, education, and national unity. While the national language represents the broader linguistic identity of a nation, the  literary  variant  serves  as  its  standardized  and  formal  expression.  The  article highlights the distinctions and interdependence of these two forms and emphasizes the importance  of  promoting  the  literary  variant  in  education,  media,  and  public  life. Challenges  related to  globalization  and  the  influence of foreign  languages are  also discussed, along with suggestions for preserving linguistic heritage.